Home truths about child sexual abuse : influencing policy and practice : a reader / edited by Catherine Itzin. - Itzin, Catherine, 1944- (Routledge, 2000)
Home Truths About Child Sexual Abuse brings together the findings of research and clinical work by experts in the UK and USA. It explores the prevalence of child exploitation and sexual abuse by men both within and outwith the family.